Differences in change of direction speed and deficit between male and female national rugby sevens players - Freitas, T. T.; Alcaraz, P. E.; Calleja-González, J.; Arruda, A. F.; Guerriero, A.; Kobal, R.; Reis, V. P.; Pereira, L. A.; Loturco, I. (The Journal of Strength and Conditioning Research, 2021)
The aims of this study were to assess the change of direction (COD) deficit in different tasks and to investigate the differences in COD ability and COD deficit between male and female rugby sevens players. Thirty-six elite rugby players from the Brazilian National senior sevens teams (18 males and 18 females) completed the following physical assessments: squat and countermovement jumps; drop jump from a 45-cm height; horizontal single and triple jumps; 40-m linear sprint; Pro-agility, L-drill, and Zig-zag COD tests; and 1 repetition maximum test in the squat exercise. The differences between male and female performances were determined using magnitude-based inferences, an independent t test, and effect sizes (ES). Pearson's product-moment correlations were performed to determine the relationships among the different COD velocities and COD deficits. Men demonstrated likely to almost certainly significantly higher performances than women in all speed-power assessments and COD tasks (ES ranging from 0.61 to 2.09; p < 0.05), with the exception of the Zig-zag drill (ES = 0.24; p > 0.05). Furthermore, males displayed significantly greater COD deficits in all tests and higher sprint momentum (ES ranging from 0.78 to 2.95; p < 0.05). Large significant relationships among COD velocities (r ranging from 0.71 to 0.88; p < 0.05) and almost perfect significant correlations among all COD deficits (r ranging from 0.90 to 0.95; p < 0.05) were obtained in both sexes. The present results indicate that male rugby players are less efficient at changing direction, relative to their maximum sprint velocity. In addition, the correlations between the different COD deficits and COD speeds suggest that elite rugby players demonstrate similar ability to change direction, independently of the angle of directional change. From a practical perspective, this implies that a more comprehensive training strategy including eccentric exercises, acceleration-deceleration drills, and directional change technique is warranted to improve the COD ability (and reduce the COD deficit) of faster and more powerful rugby sevens players.